2014
DOI: 10.1523/jneurosci.5200-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Microglial Activation Is Neuroprotective in a Mouse Model of Human Retinitis Pigmentosa

Abstract: Retinitis pigmentosa (RP) is a photoreceptor-degenerative disease caused by various mutations and is characterized by death of rod photoreceptor cell followed by gradual death of cone photoreceptors. The molecular mechanisms that lead to rod and cone death are not yet fully understood. Neuroinflammation contributes to the progression of many chronic neurodegenerative disorders. However, it remains to be determined how microglia contribute to photoreceptor disruption in RP. In this study, we explored the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
226
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(246 citation statements)
references
References 54 publications
13
226
1
Order By: Relevance
“…Previous studies showed that microglial cells infiltrate into the ONL concomitantly or before the onset of photoreceptor cell death in animal models of RP (32). In the present investigation, the double immunostaining for 8-oxoG and Iba-1 revealed that part of the 8-oxoG signal was colocalized with that of Iba-1 in both the rd10;Mutyh +/+ and rd10;Mutyh −/− mice at P17 ( Figure 4A).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Previous studies showed that microglial cells infiltrate into the ONL concomitantly or before the onset of photoreceptor cell death in animal models of RP (32). In the present investigation, the double immunostaining for 8-oxoG and Iba-1 revealed that part of the 8-oxoG signal was colocalized with that of Iba-1 in both the rd10;Mutyh +/+ and rd10;Mutyh −/− mice at P17 ( Figure 4A).…”
Section: Resultssupporting
confidence: 71%
“…We recently reported that the ocular inflammatory levels of RP patients are negatively correlated with visual function (36,37). In animal models of RP, it was shown that microglia migrate into the ONL at the onset of or before photoreceptor cell death (10,38), and the suppression of microglial activation ameliorates photoreceptor cell loss (32). However, the mechanisms underlying microglial activation in RP have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…First, our direct rescue of rods reduced the level of cell death in the RP retinae, which may lead to an increase in positive trophic factors (39) and a decrease in toxic factors. For example, we demonstrated that gene therapy reverses Müller glial cell activation ( Figure 5 and Supplemental Figure 2), which, by itself, is likely to exert a positive impact on cell survival (40).…”
Section: Creert2mentioning
confidence: 86%
“…This could lead to oxidative stress in the ONL (Zeng et al, 2014) and subsequent apoptosis (Carmody and Cotter 2000;Carmody et al, 1999), as photoreceptors are highly sensitive to changes in oxygen levels (Wellard et al, 2005). In support of this, anti-oxidants and antiinflammatories have been shown to slow photoreceptor cell death in rd10 mice (Komeima et al, 2007;Peng et al, 2014). Future studies will therefore be aimed at further understanding the role that microglia play in the course of degeneration in the rd10 retina.…”
Section: Microgliamentioning
confidence: 94%
“…In the rd10 mouse it has recently been shown that depleting microglia as well as inhibiting microglial phagocytosis resulted in increased protection of mutated photoreceptors (Zhao et al, 2015). It has also been shown in other mouse models of RP that NADPH oxidase activation in microglia resulted in rod cell death (Zeng et al, 2014) and inhibition of reactive gliosis prevents apoptosis of retinal neurons and provides neuroprotection (Ganesh and Chintala 2011;Peng et al, 2014). Interestingly, we also know that increased levels of reactive oxygen species are found in the ONL of rd10 retinas (Bhatt et al, 2010), potentially due to activated microglia.…”
Section: Microgliamentioning
confidence: 98%